The effect of grooming on plant reproduction: a theoretical approach - Marcelo, Vanessa Gonzaga (2023)
Plants that offer pollen as a resource face a dilemma, as the same pollen serves both as the carrier of male gametes and as a resource exploited by floral visitors. Some visitors, like bees, have structures specialized in pollen collection and are capable of grooming. Pollinator grooming behavior has been referred to as one of the biggest barriers to male success, affecting pollen fates. Another factor that can affect the fate of pollen is variation in the position and/or morphology of reproductive organs, as it can affect pollen placement by anthers on the pollinator body and pollen deposition on the stigma. To date, only a few theoretical investigations have attempted to model the effect of grooming on pollen transfer, and empirical studies have been limited to species in which pollen movement can be tracked. Thus, due to challenges in tracking individual pollen grains, we do not know the effect of grooming and variations in reproductive organs on pollen transfer and mating between individuals of a flower population. We use a spatially explicit agent-based modeling (ABMs) approach to determine the effect of pollen redistribution and removal in the “pollen landscape” on the vector body, affecting plant reproductive success and mating between floral individuals, associated with variation in reproductive organs. For this, we simulate visits of pollen vectors to a sequence of different flowers in a population. In our first chapter, we showed that pollen redistribution and removal restructure the pollen landscape in the body of the bee, in a way that increases the pollen delivery in consecutive visits and the number of pollen donors deposited on the stigmas. Therefore, unexpectedly, grooming can have a positive effect on male and female reproductive success during plant reproduction. In the second chapter, the mating networks were affected both by the grooming behavior and by the morphological variation of the reproductive organs, with the grooming making populations less connected and more specialized. The absence of grooming, together with the variation in the positioning of the stigma, makes populations more connected and generalist. The 2 grooming behavior breaks the dominance of some individuals observed in the absence of grooming, making the relationships between individuals better distributed. Floral individuals visited by vectors without grooming and that have variation in stigma position are reproductively more generalists. Our model predicts that species pollinated by non-grooming vectors are more variable in stigma position than species pollinated by grooming vector. However, empirical studies will be necessary to prove the hypotheses we generated with our model, allowing greater knowledge of the effects suffered by the male component that can affect pollen transfer.